GENETIC VARIABILITY, HERITABILITY AND CORRELATION STUDY IN STEM AMARANTH (Amaranthus tricolor) (Bangladesh Journal of Plant Breeding and Genetics, 2012)
Genetic variability, heritability and correlation analysis were done for yield and its component characters in twenty two (22) diverse genotypes of stem amaranth. The highest PCV (87.85%) and GCV (81.67%) were observed for primary branches per plant while the lowest PCV (10.28%) was found in plant height and the lowest GCV (7.51%) was found in leaf width. Heritability estimates in broad sense were higher for leaf weight per plant (91.10%) followed by leaves per plant (86.83%), primary branches per plant (86.42%), stem weight per plant (82.56%) and yield per hectare (78.70%). Leaf weight per plant, stem weight per plant and yield per hectare exhibited high value of heritability (91.10%, 82.56% and 78.70%) along with high genetic advance (49.38%, 134.12% and 56.00%), respectively. Leaves per plant, stem diameter, stem weight per plant, leaf weight per plant and plant height exhibited highly significant positive correlation with yield per hectare both at genotypic and phenotypic level. Selection based on these traits would give better response for the improvement in marketable yield in stem amaranth.DOI: http://dx.doi.org/10.3329/bjpbg.v25i2.18664